F-2-Deoxy-2-Fluoro-D-Glucose Positron Emission Tomography, Computed Tomography, and Magnetic Resonance Imaging for the Detection of Experimental Colorectal Liver Metastases - Gabie M. de Jong; Thijs Hendriks; Robert P. Bleichrodt; Helena M. Dekker; Roel D.M. Mus; Martin Gotthardt; Eric P. Visser; Wim J.G. Oyen; Otto C. Boerman (Molecular Imaging)
During the treatment of colorectal liver metastases, evaluation of treatment efficacy is of the utmost importance for decision making. The aim of the present study was to explore the ability of preclinical imaging modalities to detect experimental liver metastases. Nine male Wag/Rij rats underwent a laparotomy with intraportal injection of CC531 tumor cells. On days 7, 10, and 14 after tumor induction, sequential positron emission tomography (PET), computed tomography (CT), and magnetic resonance imaging (MRI) scans were acquired of each rat. At each time point, three rats were euthanized and the metastases in the liver were documented histologically. Topographically, the liver was divided into eight segments and the image findings were compared on a segment-by-segment basis with the histopathologic findings. Sixty-four liver segments were analyzed, 20 of which contained tumor deposits. The overall sensitivity of PET, CT, and MRI was 30%, 25%, and 20%, respectively. For the detection of tumors with a histologic diameter exceeding 1 mm ( n = 8), the sensitivity of PET, CT, and MRI was 63%, 38%, and 38%, respectively. The overall specificity of PET, CT, and MRI was 98%, 100%, and 93%, respectively. This study showed encouraging detectability and sensitivity for preclinical imaging of small liver tumors and provides valuable information on the imaging techniques for designing future protocols.